Delaıre's Archıtectural And Structural Cranıo-Facıal Analysıs In Cephalometric Evaluatıon - Servet Doğan; Nazmi Ertürk (Galenos Yayinevi, 1989)
In this study, the main rules of architectural and structural cranio-facial analysis developed by Delaire is explained. This architectural and structural cranio-facial analysis of the lateral cephalometric radiograph clarifies the mutual balance of the various bony structures of the cranium and face, individualizes certain of the structures, and specifies their normal of pathologic relationships. Five cephalometric, films were evaluated according to Delaire's architectural and structural analysis and according to classic cephalometric analysis. The results we obtained are presented.